2019
DOI: 10.5829/ije.2019.32.10a.08
|View full text |Cite
|
Sign up to set email alerts
|

Damage Assessment of Reinforced Concrete Buildings Considering Irregularities (RESEARCH NOTE)

Abstract: Structural damage can be controlled in performance based seismic design (PBSD) according to the requirement under a certain hazard level. During strong ground motion (GM) such buildings suffer minor to major damages depending on the shaking level of GM. The available damage assessment methods are complex, tedious and time-consuming procedure. In the present study, a simplified empirical model has been proposed that computes the GDI in a single step using the engineering demand parameters (EDPs) namely joint ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…The structural damage assessment of FRC has not been explored yet. It is very essential to determine the damage index (31)(32)(33)(34)(35)(36)(37)(38) of FRC for different percentage of fibre under different types of static and dynamic load. The investigation results from damage assessment may explore new important direction of research.…”
Section: Damage Assessmentmentioning
confidence: 99%
“…The structural damage assessment of FRC has not been explored yet. It is very essential to determine the damage index (31)(32)(33)(34)(35)(36)(37)(38) of FRC for different percentage of fibre under different types of static and dynamic load. The investigation results from damage assessment may explore new important direction of research.…”
Section: Damage Assessmentmentioning
confidence: 99%
“…The MDOF building is converted to an ESDOF and the properties of ESDOF system are determined by using Equations ( 9) to (11).…”
Section: Design Philosophy Usedmentioning
confidence: 99%
“…Also Hait et al (9) confirmed that the buildings with irregular configurations suffer greater damage than those with regular contours, mainly due to the increased influence of torsional effects.…”
Section: Introductionmentioning
confidence: 96%